2022
DOI: 10.1021/acs.inorgchem.2c00194
|View full text |Cite
|
Sign up to set email alerts
|

Phosphinate MOFs Formed from Tetratopic Ligands as Proton-Conductive Materials

Abstract: Metal–organic frameworks (MOFs) are attracting attention as potential proton conductors. There are two main advantages of MOFs in this application: the possibility of rational design and tuning of the properties and clear conduction pathways given by their crystalline structure. We hereby present two new MOF structures, ICR-10 and ICR-11, based on tetratopic phosphinate ligands. The structures of both MOFs were determined by 3D electron diffraction. They both crystallize in the P3̅ space group and contain arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…26,27 In recent years, our group presented a series of MOFs called ICR (Institute of Inorganic Chemistry Řež) derived from ligands containing phosphinate groups. 28,29 We proved that similarly to carboxylates phosphinate ligands can be also used for the formation of predictable structures. A phosphinate group possesses an additional alkyl or aryl group bonded to the phosphorus atom.…”
Section: Introductionmentioning
confidence: 90%
“…26,27 In recent years, our group presented a series of MOFs called ICR (Institute of Inorganic Chemistry Řež) derived from ligands containing phosphinate groups. 28,29 We proved that similarly to carboxylates phosphinate ligands can be also used for the formation of predictable structures. A phosphinate group possesses an additional alkyl or aryl group bonded to the phosphorus atom.…”
Section: Introductionmentioning
confidence: 90%
“…26,27 In recent years, we have presented a series of MOFs called ICR (Institute of Inorganic Chemistry R ̌ez) derived from ligands containing phosphinate groups. 28,29 Our research has demonstrated that, similar to carboxylates, phosphinate ligands can also be employed to form predictable structures. A phosphinate group possesses an additional alkyl or aryl group bonded to the phosphorus atom.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Phosphinate groups bind to high-valent metals with a stronger bond than commonly used carboxylic groups. Since they also have only two accessible oxygen atoms for bonding, the formed structures are more predictable than in the case of phosphonate ligands with three accessible oxygen atoms. , In recent years, we have presented a series of MOFs called ICR (Institute of Inorganic Chemistry Řež) derived from ligands containing phosphinate groups. , Our research has demonstrated that, similar to carboxylates, phosphinate ligands can also be employed to form predictable structures. A phosphinate group possesses an additional alkyl or aryl group bonded to the phosphorus atom.…”
Section: Introductionmentioning
confidence: 99%
“…Since the late 1990s, a whole new field of application as proton-conducting materials has opened up. , There are two types of proton-conducting MOFs: one is based on water; the operating temperature is generally 20–80 °C, and the proton conductivity is between 10 –2 and 10 –8 S·cm –1 . The other is in the anhydrous state, where the working temperature is generally 100–250 °C, and the proton conductivity is between 10 –2 and 10 –6 S·cm –1 . , No matter what the conditions are, the effective hydrogen bonding path is the most critical. In addition, MOFs are easy to prepare and can form composites with other materials, thus improving their chemical stability and proton conductivity.…”
mentioning
confidence: 99%
“…The other is in the anhydrous state, where the working temperature is generally 100−250 °C, and the proton conductivity is between 10 −2 and 10 −6 S•cm −1 . 21,22 No matter what the conditions are, the effective hydrogen bonding path is the most critical. In addition, MOFs are easy to prepare and can form composites with other materials, thus improving their chemical stability and proton conductivity.…”
mentioning
confidence: 99%